Conflict and Recognition in Munier Choudhury’s Kobor (Spectrum, 2022)
The emergence of Bangladesh as a nation is a culmination of long drawn out struggles faced by the Bengalis of the region, which has been portrayed in a vast body of Bengali literature. The West Pakistani suppression of young Bangla speaking voices in 1952 is resisted back through powerful and symbolic returns of the dead in the play Kobor (Grave) by Munier Choudhury, which was first written and produced in jail in 1953 in the context of the Language Movement of 1952. This paper explores Kobor to address the conflicts, power dynamics and resolution of conflicts that have been at the centre of Bengali identity formation and recognition during Pakistani rule. Conflict theory examines tensions that arise due to cultural, political and racial differences and the subsequent intensity of conflicts that concomitantly increases with the degree of unity in the resistant groups. A critical analysis of Kobor from the perspectives of conflict theory reveals inter-state ideological conflicts which were fuelled by the cultural, linguistic, political and other socioeconomic differences and disparities between the two wings of Pakistan.Spectrum, Volume 16, June 2021: 40-52